Prognostic relevance of programmed cell death protein 1/programmed death-ligand 1 pathway in thymic malignancies with combined immunohistochemical and biomolecular approach. (1st September 2020) - Berardi, Rossana; Goteri, Gaia; Brunelli, Alessandro; Pagliaretta, Silvia; Paolucci, Vittorio; Caramanti, Miriam; Rinaldi, Silvia; Refai, Majed; Pompili, Cecilia; Morgese, Francesca; Torniai, Mariangela; Marcantognini, Giulia; et al.
ABSTRACT: Background: The aim of the study was to investigate Programmed cell Death protein 1 (PD-1) and Programmed Death-Ligand 1 (PD-L1) and their mRNA expression in thymic epithelial tumors (TETs). Research design and methods: We analyzed 68 samples of formalin-fixed paraffin-embedded tissue (63 thymomas and 5 thymic carcinomas). PD-1 and PD-L1 protein expression were evaluated by immunohistochemistry, and mRNA expression was evaluated by real-time PCR. Results: M/F ratio was 33/35, and median age was 60.5 years. Twenty patients had Myasthenia Gravis (MG). In the subgroup with large tumors (>5 cm), PD-L1 mRNA overexpression was significantly associated with worse prognosis vs. patients with no mRNA overexpression (p = 0.0083) and simultaneous PD-L1 immunostaining (>1%); PD-L1 mRNA overexpression was significantly associated with worse prognosis, respect to patient with PD-L1 negative immunostaining, and no PD-L1 mRNA overexpression (p = 0.0178). The elderly patients (>60 years) with large tumors showed worse prognosis (p = 0.0395). PD-L1 immunostaining (>50%) resulted to be significantly associated with MG. Conclusions: Our data suggest the potential involvement of the PD-1 and PD-L1 pathway in TETs' progression. According to our results, it may be helpful to design future trials with anti-PD-1 drugs to establish high-risk patients after surgery.